Potentiality of water resources in the Kirala Kele Partial-nature-based wetland of Southern Sri Lanka - Sudusingha Liyanage, Jothirathna Fernando (Advances in Social Sciences Research Journal, 2019)
The semi nature based wetlands are areas characterized by a high percentage of artificial environments, which are saturated with water, either permanently or seasonally, it determines the nature of soil development and the types of animals and plant communities in the soil. Sri Lanka can earn more benefits such as being able to provide direct financial benefits for conservation and management of wetlands, financial benefits and empowerment for local people, and build environmental and cultural awareness of how to sustain the resources of wetlands. This paper explores the potential water resources of the partial-nature-based wetland at Kirala Kele for the long-term development. The evaluation process of the water resources was based on six main criteria, including surface water, rainfall, relative humidity, evapo-transpiration, terrain and ground water of the area. Those factors were generated from the land use/land cover map and field observation with GPS points. The spatial and temporal changes in the wetland area from 1983 to 2011 were analyzed using satellite remote sensing and GIS. There has been a positive correlation and significant relationship between relative humidity (RH) and rainfall (RF) in the Kirala Kele wetland area for thirty four years.